Comparison of the Effectiveness of Single-Visit and Multi-Visit Root Canal Treatment on Healing Intraoral Sinus Tract - Fatma Begüm Peker; Mehmet Burak Güneşer (International Journal of Dentistry, 2025)
Conclusion: Both SV and MV root canal treatments (RCTs) yielded comparable outcomes in terms of postoperative pain levels and the time necessary for sinus tract resolution, with no statistically significant differences observed between the two approaches. The observed similarity in healing parameters and pain levels suggests that both treatment methods demonstrate comparable clinical effectiveness.